Tactical construction of the 200 m run in competition conditions (falscher Titel: Pre-seasonal training methods for academic basketball sport clubs) - Mirzoev, O. M.; Mukhin, O. M. (Theory and Practice of Physical Culture, 2019)
The article is devoted to the tactical training in 200 m running in terms of competitions held at a stadium. The distance was conditionally divided into several interconnected segments (sections). We analyzed the peculiarities of running on the studied distance segments (sections) and the sprinters` functional state when running a curve (0-100 m) and on a straight segment (100-200 m), as well as the distribution of (applied) forces, etc. The multiannual studies of the competitive performance in elite sprint sport give grounds for the following recommendations: